Activity and MeCP2‐dependent regulation of nNOS levels in enteric neurons. Issue 11 (2nd June 2016) - Wahba, G.; Schock, S. C.; Cudd, S.; Grynspan, D.; Humphreys, P.; Staines, W. A.
Abstract: Background: Rett syndrome (RTT) is a neurological disorder characterized by severe cognitive impairment, motor dyspraxia, and seizures. Rett syndrome arises predominantly from mutations in MECP2, the gene coding for methyl‐CpG‐binding protein 2 (MeCP2). MeCP2 is an important mediator of synaptic development and is essential in regulating homeostatic synaptic plasticity (HSP) in the brain. In addition to demonstrating central nervous system impairment, RTT patients also suffer from gastrointestinal (GI) dysmotility. We hypothesize that this is due to a similar impairment of plasticity‐dependent synaptic function in the enteric nervous system (ENS). We recently reported that MeCP2 is expressed in the ENS, providing evidence that neuronal dysfunction may mediate the GI pathology. Methods: Baseline measures of MeCP2‐KO vs wild‐type (WT) GI neuronal nitric oxide synthase (nNOS) were assessed in tissue samples and in vitro . Experiments were carried out to measure nNOS in baseline vs activated plasticity states in vitro . Functional in vivo studies were carried out to determine whether MeCP2‐KO mice reproduced the RTT GI hypomotility. Key Results: Methyl‐CpG‐binding protein 2‐KO mice reproduced the GI hypomotility seen in RTT. MeCP2‐KO GI tissue demonstrated elevated nNOS levels. Cultured WT enteric neurons showed upregulation of nNOS following moderate, prolonged stimulation by hyperkalemia; neurons from MeCP2‐KO mice failed to show this nNOS upregulation. Conclusions & Inferences: MeCP2 is required for proper GI motility and normal nNOS levels. Neuronal nitric oxide synthase imbalances could mediate the GI dysmotility seen in RTT. Disruption of MeCP2‐dependent HSP may be the basis for aberrant nNOS levels and hence GI dysmotility in MeCP2‐KO and RTT. Abstract : MeCP2 is required for proper GI motility and normal nNOS levels. nNOS imbalances could mediate the GI dysmotility seen in RTT. Disruption of MeCP2‐dependent HSP may be the basis for aberrant nNOS levels and hence GI dysmotility in MeCP2‐KO and RTT.